Exploring the distribution and co-occurrence of rpf-like genes and nitrogen-cycling genes in water reservoir sediments - Hou, Aiqin; Fu, Huayi; Liu, Leilei; Su, Xiaomei; Zhang, Shusheng; Lai, Jiahou; Sun, Faqian (Frontiers in Microbiology, 2024)
Water reservoir sediments represent a distinct habitat that harbors diverse microbial resources crucial for nitrogen cycling processes. The discovery of resuscitation promoting factor (Rpf) has been recognized as a crucial development in understanding the potential of microbial populations. However, our understanding of the relationship between microorganisms containing rpf-like genes and nitrogencycling functional populations remains limited. The present study explored the distribution patterns of rpf-like genes and nitrogen-cycling genes in various water reservoir sediments, along with their correlation with environmental factors.Additionally, the co-occurrence of rpf-like genes with genes associated with the nitrogen cycle and viable but non-culturable (VBNC) formation was investigated. The findings indicated the ubiquitous occurrence of Rpf-like domains and their related genes in the examined reservoir sediments. Notably, rpf-like genes were predominantly associated with Bradyrhizobium, Nitrospira, and Anaeromyxobacter, with pH emerging as the primary influencing factor for their distribution. Genera such as Nitrospira, Bradyrhizobium, Anaeromyxobacter, and Dechloromonas harbor the majority of nitrogen-cycling functional genes, particularly denitrification genes. The distribution of nitrogen-cycling microbial communities in the reservoir sediments was mainly influenced by pH and NH4 + . Notably, correlation network analysis revealed close connections between microorganisms containing rpf-like genes and nitrogen-cycling functional populations, as well as VBNC bacteria. These findings offer new insights into the prevalence of rpf-like genes in the water reservoir sediments and their correlation with nitrogen-cycling microbial communities, enhancing our understanding of the significant potential of microbial nitrogen cycling.